Biodrying Performance and Greenhouse Gas Emissions through Hot Air Aeration in Solid Waste Conversion - Badrus Zaman; Nurandani Hardyanti; Wiharyanto Oktiawan; Budi Prasetyo Samadikun; Purwono Purwono (Universitas Diponegoro, 2026)
Biodrying can convert solid waste into Refuse Derived Fuel (RDF) as an alternative to fossil fuels. The conversion of solid waste to RDF with a moisture content of 10-30% generally takes 21 days. This study aims to analyze greenhouse gas emissions and biodrying performance by applying hot air aeration to accelerate solid waste conversion into RDF. Laboratory-scale investigation used a bio-drying reactor and a solid waste mixture. Hot air was produced by burning wood charcoal (X1) and mixture of wood charcoal and sawdust (X2). The research showed that hot air aeration systems are more efficient and effective at converting solid waste into RDF. Water content of solid waste reduce from 50% to 34.29% after 60 minutes at 47-80oC. N2O emissions were lower when the hot air source came from burning X1. CO2 emissions were lower when the hot air source came from burning X2. The amount of electrical power required to burn one kg of X1 and X2 is 0.0135 and 0.018 kWh, respectively.